The Role of Slower Vessel Speeds in Reducing Greenhouse Gas Emissions, Underwater Noise and Collision Risk to Whales - Leaper, Russell (Frontiers in Marine Science, 2019)
Reducing speeds across shipping fleets has been shown to make a substantial contribution to effective short term measures for reducing greenhouse gas (GHG) emissions, working towards the goal adopted by IMO in April 2018 to reduce the total annual GHG emission by at least 50% by 2050 compared to 2008. I review modelling work on GHG emissions and also on the relationships between underwater noise, whale collision risk and speed. I examine different speed reduction scenarios that would contribute to GHG reduction targets, and the other environmental benefits of reduced underwater noise and risk of collisions with marine life. A modest 10% speed reduction across the global fleet has been estimated to reduce overall GHG emissions by around 13% (Faber et al. 2017) and improve the probability of meeting GHG targets by 23% (Comer et al. 2018). I conclude that such a 10% could reduce the total sound energy from shipping by around 40%. The associated reduction in overall ship strike risk has higher uncertainty but could be around 50%. This would benefit whale populations globally and complement current efforts to reduce collision risk in identified high risk areas through small changes in routing.